The Relationship Between Principal Leadership, School Climate, Work Discipline, And Work Motivation With Teacher Performance In Public Elementary Schools In Ambon City And The Lease Islands - Wiliem Yacob Hetharion; Jane Gresia Akollo; Claudia Monique Pattiruhu; Meike Elsa Toisuta (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Teacher performance plays a crucial role in determining the quality of education, particularly in geographically challenging areas such as Ambon City and the Lease Islands. This study aims to examine the influence of principal leadership, school climate, work discipline, and work motivation on teacher performance in public elementary schools within this region. A quantitative approach with a correlational research design was employed, using cross-sectional data collected through structured questionnaires. The study involved 210 teachers selected through a saturated sampling technique. Data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The results show that principal leadership, school climate, work discipline, and work motivation each have a positive and significant effect on teacher performance. Additionally, principal leadership significantly influences school climate, work discipline, and motivation, while school climate also enhances teacher discipline and motivation. Work discipline further contributes positively to teacher motivation. These findings highlight the central role of leadership and organizational conditions in shaping teacher behavior. The study implies the need for continuous leadership development, strengthened school culture, and systematic motivation strategies to improve teacher performance. Future research should expand the study area and include additional variables such as job satisfaction, workload, and teacher well-being to deepen the understanding of factors affecting teacher performance.